ダイ4ジ ナンキョク チイキ カンソクタイ ウチュウセン ブモン センジョウ カンソク ホウコク - 福島, 紳; フクシマ, シン; 中村, 強; ナカムラ, ツヨシ; FUKUSHIMA, Shin; NAKAMURA, Tsuyoshi (国立極地研究所, 1961)
P(論文) The third latitude survey in cosmic-ray neutrons has been carried out along the same ship-route and by using the same apparatus as in the preceeding two surveys. Although the observation room was the same as that in the second survey, one additional room was constructed over our room. Thus, as observational conditions in the three latitude surveys are different from one another, the obtained results could not be compared in absolute intensity but in relative. The periods during which each survey was performed are represented with the corresponding sunspot relative numbers in Fig. 1, where a full curve shows the 12 months running average of monthly mean values in sunspot numbers. Fig. 2 shows 12 hour mean values for each latitude curve in the southern hemisphere. It is seen from the figure that the slope of latitude curve becomes gentle at the second survey and then almost recovers at the third. To explain such changes in primary cosmic-rays by terms of changes in solar activity represented by sunspot numbers as shown in Fig. 1, we suppose a hysteresis effect of solar activity upon cosmic-rays. In other words, changes in cosmic-rays do not immediately follow that in solar activity but about half a year later. departmental bulletin paper